Impact of Green Human Resource Management on Promoting Green Employee Behaviour in Russia: A Moderating Role of Employee empowerment - Hood Laeeq (Arthatama, 2021)
The study aimed to analyze green human resource management (HRM) on promoting green employee behaviour in Russia through the mediating role of employee empowerment. The questionnaire was dispersed among 300 respondents working as HRM managers in the industrial sector of Russia to gather their opinions. To analyze the data accumulated from participants through survey, confirmatory factor analysis, discriminant validity and quality assessment criteria has employed in this study. Furthermore, Smart PLS statistical software has been used. Findings revealed that green empowerment, government policies, and green training have a significant relationship with green employee behaviour.